Stripper model for co2 removal from iron ore reduction unit using amine scrubbing process - Peng, Hoe Hoi (2014)
Iron and steel production is a highly energy intensive process which has been reported to produce about 10% of worldwide CO2 from fossil fuel. Thus, it has become a potential industry for CO2 removal process. High energy consumption of amine scrubbing has caused the challenge for the large scale application. Even though recent studies have been done to reduce the energy consumption, there are lacking of focus on the optimization of stripper operating conditions. Thus, the objective of this research is to investigate the relationships of the stripper operating parameters on the reboiler heat duty and CO2 removal percentage in the stripper. The modeling was done by using rate-based model in Aspen Plus with “MEA Property Insert” which described a MEA-H2O-CO2 system thermodynamically with electrolyte-NRTL model. The column specifications were adapted from a pilot plant in University of Texas, Austin and the flue gas flow and compositions were adapted from Arasto et al. (2012). From the results, it showed that the increase in stripper with higher MEA concentration had reduced the reboiler duty up to 20 % and higher rich solvent temperature were able to reduce the reboiler heat duty. Besides that, the increase of stripper pressure had increased CO2 removal efficiency in the stripper yet the CO2 removal percentage was remained constant with the increase in rich solvent temperature. Lower rich solvent loadings with constant lean solvent loadings, molar flow rate of CO2 exiting the stripper and mass flow rate of MEA solvent enabled the reduction in reboiler heat duty. Even though high stripper temperature enables better performance, the stripper temperature should be maintained below 125 °C to avoid MEA degradation. Besides that, it is suggested to use lower lean solvent flow rate so that the output changes can be observed easily. Based on the results, it can be concluded that the hypotheses were accepted. The findings of this study are useful as the reference for future amine scrubbing application on the iron ore reduction unit and to reduce the energy requirement of the process